2020
DOI: 10.3390/app11010066
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacterial Potential for Restoration of Loess Surfaces through Artificially Induced Biocrusts

Abstract: Loess is a highly porous and easily erosive aeolian sediment covering approximately 10% of the Earth’s surface. The weak vegetation cover and high wind speeds in many of these regions make loess sediment the main source of dust in the atmosphere. Dust particles deteriorate air quality and affect soils, crops, water systems, and animal and human health. The commonly used method for combating desertification is revegetation. However, planting various vascular plant species in loess landscapes did not show any lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 118 publications
0
5
0
Order By: Relevance
“…For example, strains isolated from terrestrial environments have recently been reported to produce an uncommon cyanotoxin apratoxin, the production of which was previously associated exclusively with marine environments [ 7 ]. Bioassays could be a great tool to examine the general toxicity of inoculants [ 27 , 73 ], which is especially important for the rehabilitation of degraded and desertified land by cyanobacterial inoculation, since the application of toxic cyanobacterial strains would be hazardous.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, strains isolated from terrestrial environments have recently been reported to produce an uncommon cyanotoxin apratoxin, the production of which was previously associated exclusively with marine environments [ 7 ]. Bioassays could be a great tool to examine the general toxicity of inoculants [ 27 , 73 ], which is especially important for the rehabilitation of degraded and desertified land by cyanobacterial inoculation, since the application of toxic cyanobacterial strains would be hazardous.…”
Section: Discussionmentioning
confidence: 99%
“…Loess deposits, because of their porous structure and extensive exploitation and degradation, are a significant source of airborne dust affecting people living in loess-rich areas. With a similar idea to the BLOCDUST hypothesis on the interaction between cyanobacteria and loess particles, artificial formation of BLC cover over the degraded loess surfaces by inoculation of cyanobacteria is proposed as a promising mechanism for their restoration [ 26 , 27 ]. The technology is based on the inoculation of laboratory-grown cyanobacteria on disturbed soil surfaces to establish soil particle stability, nutrient uptake, and circulation, and promote the establishment of higher vegetation [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not all cyanobacteria are harmful, and they perform crucial ecosystem services. Palanački Malešević et al assessed the potential of cyanobacterial inoculation for the restoration of damaged loess surfaces through assisted development of biological loess crusts (BLCs) [5]. A number of cyanobacterial strains were screened for desirable characteristics in the restoration process (lack of toxicity, and high production of biomass and polysaccharides).…”
Section: Antosiak Et Al Described Different Responses In Gene Express...mentioning
confidence: 99%
“…In Cu-deficient areas, ataxia in lambs can be as high as 30% in some areas. Although deaths were rare, sheep failed to thrive, resulting in severe economic losses [6][7][8]. Cu deficiency includes direct and induced deficiencies.…”
Section: Introductionmentioning
confidence: 99%